Role of Sagittal and Oblique Smiling Profiles in Evaluating Facial Esthetics. Issue 2 (March 2015) - Yang, Xianrui; Yi, Yating; Yang, Shuying; Xue, Chaoran; Wang, Yuan; Chen, Mingjia; Han, Xianglong; Bai, Ding
<x xml:space="preserve">Abstract</x> Introduction Surgeons and orthodontists used to use a conventional set of facial photographs, composed of front, front smiling, and profile images to evaluate facial esthetics, whereas sagittal and oblique smiling profile images have been largely neglected in practice. The aim of this study was to explore the importance of sagittal and oblique smiling profiles in evaluating facial esthetics. Methods Photographs from 80 patients, of whom 40 underwent orthognathic surgery and 40 underwent orthodontic treatment, including front, front smiling, profile, sagittal profile smiling, and oblique profile smiling images before and after treatment, were collected and synthesized into 6 categories. Thirty judges gave scores to these photographs based on their own esthetic conception with a 1-week interval for each category. Results The results demonstrated that the mean score change of evaluating facial attractiveness of patients who underwent orthognathic surgery was lower when adding sagittal or oblique smiling profiles before the treatment, whereas it was higher after the treatment, which were opposite to the orthodontic treatment group with a higher score before the treatment and a lower score after the treatment when sagittal or oblique smiling profiles were added. The changes have a significant difference in adding both sagittal smiling profiles (P < 0.05) and oblique smiling profiles (P < 0.05) before and after treatment. Conclusions Along with oblique smiling profile, sagittal smiling profile is crucial in evaluating facial esthetics for orthodontic treatment and orthognathic surgery. Both of them suggested to be integrated in routine photographic assessment of facial attractiveness evaluation before and after treatment, especially in orthognathic surgery for facial esthetic evaluation.